The Impact of Social Media on Political Awareness and Voter Turnout in Delta State - Ejiroghene, Ayewumi Tamarasere; Chuks, Okolie Ugo (Journal of Southern Sociological Studies, 2026)
This study investigated the impact of social media on political awareness, voter turnout, and voter participation among residents of Delta State, Nigeria. Specifically, it examined how social media usage influences individuals' knowledge of political processes, their motivation to vote, and their attitudes toward political engagement. Data were collected from 341 respondents using a structured questionnaire designed to measure the relationship between social media and three key political variables. Pearson correlation analysis revealed strong and statistically significant positive relationships between social media use and political awareness, voter turnout, and voter attitudes and participation. These findings indicate that social media plays a vital role in enhancing political consciousness, encouraging electoral participation, and shaping voter behavior in the digital age. The study concludes that leveraging social media platforms can serve as an effective strategy for promoting civic engagement and strengthening democratic participation in the region. Recommendations were offered for policymakers, electoral bodies, and civic organizations to maximize the positive influence of social media while addressing potential limitations.